2021
DOI: 10.2196/27634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Message Framing on Cancer Prevention and Detection Behaviors, Intentions, and Attitudes: Systematic Review and Meta-analysis

Abstract: Background With the increasing health care burden of cancer, public health organizations are increasingly emphasizing the importance of calling people to engage in long-term prevention and periodical detection. How to best deliver behavioral recommendations and health outcomes in messaging is an important issue. Objective This study aims to disaggregate the effects of gain-framed and loss-framed messages on cancer prevention and detection behaviors and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…To promote mental health for everyone, everywhere, the World Health Organization’s most recent global mental health report strives to motivate and guide revolutionary action [ 1 , 2 ]. According to estimates by the World Health Organization, in the first year of the COVID-19 pandemic, the incidence of both depression and anxiety disorders increased by more than 25% [ 3 ]. However, mental health services are few and still underutilized globally [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To promote mental health for everyone, everywhere, the World Health Organization’s most recent global mental health report strives to motivate and guide revolutionary action [ 1 , 2 ]. According to estimates by the World Health Organization, in the first year of the COVID-19 pandemic, the incidence of both depression and anxiety disorders increased by more than 25% [ 3 ]. However, mental health services are few and still underutilized globally [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, previous observation protocols focused on the content of communication, and studies assessing form have been mainly experimental rather than observational (e.g. [ 41 , 42 ]). Since little is known about how linguistic elements are used in real-life clinical interactions, this paper introduced a carefully developed coding protocol to quantify communication form.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous survey ( 46 ), we observed a baseline proportion of healthy lifestyle adherence at approximately 30% among participants with familiar sample characteristics. For the intervention groups, we anticipate a relative increase of at least 50% ( 47 ), with an expected difference of 25% between the gain- and loss-framed groups ( 39 ). This corresponds to an estimated effect size (W) for Chi-square of 0.20 ( 48 ), aligning closely with recommendations from prior studies ( 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, conflicting findings have emerged regarding the comparative benefits of positive/gain- versus negative/loss-framed messages ( 33 ). For example, loss-framed messages have been confirmed to persuade people to adopt cancer detection behaviors ( 39 ) and diabetes self-care ( 40 ), while gained-framed messages have received considerable empirical support for physical activity and dental hygiene behaviors ( 37 ). In addition, the literature on message framing consistently demonstrated that when a behavior or characteristic of the individual is not taken into account, there is no discernible advantage for gain- or loss-framed messages ( 41 ).…”
Section: Introductionmentioning
confidence: 99%